Determination of Hotel Tax Revenue Targets (Case Study in Sumedang Regency) - TRESNAJAYA, Rd. Tatan Jaka; SUPRIYADI, Supriyadi; SABNITA, Nina (PT Keberlanjutan Strategis Indonesia, 2024)
Sumedang Regency, located in West Java, leverages its geographical and economic potential to enhance regional income through the management of over 40 tourist destinations and support for 475 MSMEs. Hotel tax revenue, a key component of regional income, fluctuated between 2019 and 2023, influenced by factors such as tourist numbers, room occupancy rates, and GRDP. This study aims to analyze the determinants of hotel tax revenue in Sumedang Regency within the framework of the HKPD Law, providing insights for optimizing regional revenue and supporting autonomy. Using a combination of qualitative and quantitative approaches, the study explores the impact of various factors, including GRDP, accommodation and food services, human development index, hotel availability, and population, on hotel tax revenue. Qualitative findings highlight the importance of sectoral development policies, particularly focusing on tourism and economic indicators, while quantitative analysis introduces a model called the “Calculator.” This tool aids in setting tax revenue targets and evaluating outcomes, offering the Sumedang Regency Government a data-driven approach to improving tax management and regional financial performance.